Stable H and O isotope-based investigation of moisture sources and their role in river and groundwater recharge in the NE Carpathian Mountains, East-Central Europe†. Issue 2 (4th March 2019) - Bădăluță, Carmen-Andreea; Perșoiu, Aurel; Ionita, Monica; Nagavciuc, Viorica; Bistricean, Petruț-Ionel
ABSTRACT: The region situated between the mountain area and the lowlands in NE Romania (East-Central Europe) is experiencing increased competition for water resources triggered by a growing population, intensification of agriculture, and industrial development. To better understand hydrological cycling processes in the region, a study was conducted using stable isotopes of water and atmospheric trajectory data to characterize regional precipitation and vapour sources derived from the Atlantic Ocean, Mediterranean and Black Seas, as well as recycled continental moisture, and to assess and partition these contributions to recharge of surface and groundwater. Atmospheric moisture in the lowlands is found to be predominantly delivered along easterly trajectories, while mountainous areas appear to be dominated by North Atlantic Ocean sources, with moisture transported along mid-latitude, westerly storm tracks. Large-scale circulation patterns affect moisture delivery, the North Atlantic Oscillation being particularly influential in winter and the East Atlantic pattern in summer. Winter precipitation is the main contributor to river discharge and aquifer recharge. As winter precipitation amounts are projected to decrease over the next decades, and water abstraction is expected to steadily increase, a general reduction in water availability is projected for the region.